Diffusion tensor imaging in pediatric Chiari type I malformation. (13th May 2014) - Eshetu, Tadesse; Meoded, Avner; Jallo, George I; Carson, Benjamin S; Huisman, Thierry AGM; Poretti, Andrea
<x xml:space="preserve">Abstract</x> Aim Chiari type I malformation (C1M) may be symptomatic or asymptomatic as an incidental finding. In this retrospective study, we applied diffusion tensor imaging (DTI) to study the brainstem and cerebellar white matter tracts in C1M. Method Diffusion tensor imaging (DTI) data were acquired on a 1.5T MR‐scanner using balanced pairs of diffusion gradients along 20 non‐collinear directions. Measurements from regions of interest in each pontine corticospinal tract, medial leminscus, and middle cerebellar peduncle (MCP) and in the lower brainstem were obtained for fractional anisotropy and mean, axial, and radial diffusivity. Values in symptomatic and asymptomatic children, and children with and without hydromyelia were compared using analysis of variance. Results Fifteen children with C1M (10 males, five females; six symptomatic [four with hydromyelia] and nine asymptomatic) were included. Median age was 6 years 5 months (range 2y 10mo–15y 4mo). No significant differences in DTI scalars were found in the lower brainstem. In both MCPs, axial diffusivity values were lower in symptomatic than in asymptomatic children (p=0.049 and p=0.035 respectively) and higher in children with hydromyelia versus without hydromyelia (p=0.018 and p=0.006 respectively). In the left MCP, mean diffusivity values were lower in symptomatic than in asymptomatic children (p=0.047). Interpretation Our results show that microstructural tissue alterations may be present in C1M. Additionally, our study suggests a specific role for the MCPs in C1M. Further large‐scale studies are warranted.